Pimobendan Inhibits HBV Transcription and Replication by Suppressing HBV Promoters Activity - Yuan, Si-Yu; Yu, Hai-Bo; Yang, Zhen; Qin, Yi-Ping; Ren, Ji-Hua; Cheng, Sheng-Tao; Ren, Fang; Law, Betty Yuen Kwan; Wong, Vincent Kam Wai; Ng, Jerome P. L.; Zhou, Yu-Jiao; He, Xin; et al. (Frontiers in Pharmacology, 2022)
Current anti-HBV therapeutic strategy relies on interferon and nucleos(t)ide-type drugs with the limitation of functional cure, inducing hepatitis B surface antigen (HBsAg) loss in very few patients. Notably, the level of HBsAg has been established as an accurate indicator to evaluate the drug efficacy and predict the disease prognosis, thus exploring a novel drug targeting HBsAg will be of great significance, herein, by screening 978 compounds from an FDA-approved drug library and detected the inhibitory function of each drug on HBsAg level in HepG2.2.15 cells supernatant, we identified that Pimobendan has a powerful antiviral activity but a relatively low cytotoxicity. The inhibitory effects of Pimobendan on HBsAg as well as other HBV markers were validated in HBV-infected cell models and HBV-transgenic mice. Mechanistically, Real-time PCR and Dual-Luciferase reporter assay were used to identify the regulation of Pimobendan on cccDNA transcription was partially related to transcription factor CAAT enhancer-binding protein α (C/EBPα). That is, Pimobendan inhibited HBV transcription through suppressing HBV promoters, subsequently reduced HBV RNAs levels and HBsAg production. In conclusion, Pimobendan was identified to be a transcription inhibitor of cccDNA, inhibiting HBsAg and other HBV replicative intermediates both in vitro and in vivo. This report may provide a promising lead for the development of new anti-HBV agent.